2018
DOI: 10.1002/jcp.26460
|View full text |Cite|
|
Sign up to set email alerts
|

Blocking PI3K/AKT signaling inhibits bone sclerosis in subchondral bone and attenuates post‐traumatic osteoarthritis

Abstract: PI3K/AKT signaling is essential in regulating pathophysiology of osteoarthritis (OA). However, its potential modulatory role in early OA progression has not been investigated yet. Here, a mouse destabilization OA model in the tibia was used to investigate roles of PI3K/AKT signaling in the early subchondral bone changes and OA pathological process. We revealed a significant increase in PI3K/AKT signaling activation which was associated with aberrant bone formation in tibial subchondral bone following destabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
60
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 64 publications
(98 reference statements)
2
60
1
Order By: Relevance
“…It remains to be investigated how combination therapy activates cell cycle regulators. The FAK-PI3K-AKT signaling pathway is a crucial target for the treatment of OA [81]. In previous studies, we demonstrated that acupotomy can promote cartilage anabolism by specially activating the FAK-PI3K-AKT signaling pathway [18].…”
Section: Discussionmentioning
confidence: 91%
“…It remains to be investigated how combination therapy activates cell cycle regulators. The FAK-PI3K-AKT signaling pathway is a crucial target for the treatment of OA [81]. In previous studies, we demonstrated that acupotomy can promote cartilage anabolism by specially activating the FAK-PI3K-AKT signaling pathway [18].…”
Section: Discussionmentioning
confidence: 91%
“…Allicin alleviates the progression of OA by inactivating the PI3K/AKT/NF-jB pathway [15]. Blocking PI3K/AKT signaling can reduce post-traumatic OA or tumor necrosis factor-a-induced OA [16,17]. Thus, blocking this pathway could be a promising treatment strategy for KOA.…”
mentioning
confidence: 99%
“…PI3K/AKT signaling pathway significantly regulates the function of osteoblasts and osteoclasts by influencing the formation, differentiation, proliferation and apoptosis of osteoblasts and osteoclasts (Agas, Sabbieti, Marchetti, Xiao, & Hurley, 2013; Qu et al, 2014). It has been reported that PI3K/AKT signaling pathway maintains the dynamic balance of bone tissue not only under normal conditions, but also under pathological conditions (Lin et al, 2018). Therefore, PI3K/AKT signal pathway was detected by western blot analysis in Kunming mice with osteoporosis and PSMC6 gene knockout mice with osteoporosis caused by ovariectomy, respectively.…”
Section: Discussionmentioning
confidence: 99%